Effectiveness of Schema Therapy on the Interpersonal Relationships Dimensions in Clients with Substance Dependence - Atefeh Mehdifar; Fataneh Amirmahmoudi; Hamid Sabaghian Baghdadabad; Esmaeil Zaighaminejad; Marzieh Shahabizadeh (Iranian Journal of Educational Research)
Objective: The present investigation aimed to explore the efficacy of schema therapy in enhancing the dimensions of interpersonal relationships among individuals undergoing treatment for drug addiction in the city of Sirjan (Iran). Methods: The research design employed was a semi-experimental approach, incorporating both control and experimental groups. The target population consisted of all drug addicts receiving treatment in Sirjan, while the sample size comprised 30 individuals, selected through the convenience sampling method and divided into two experimental groups (15 individuals each) and a control group (15 individuals). The experimental groups underwent schema therapy for a duration of 8 sessions, while data were collected using an interpersonal relationship questionnaire. The obtained data were subjected to statistical analysis of covariance using SPSS software version 26. Results: The findings of the data analysis revealed that the treatment protocol effectively influenced interpersonal relationships and their various dimensions, leading to improvement. Conclusion: According to our research outcomes, the implementation of schema therapy holds significant importance in the enhancement of interpersonal relationships dimensions throughout the duration of the therapeutic process for individuals receiving treatment for substance abuse.